Batara Kala Masa Kini: Transformasi Slametan Ruwatan pada Masyarakat Jawa di Malang Selatan - Dahniar, Edlin (Studi Budaya Nusantara, 2017)
Abstract This paper aims to find out how slametan Ruwatan experienced a shift, from which Java originally became ruwatan combination of Java and Islam. Ruwatan is one of slametan (salvation) to ask for the salvation that became the Javanese tradition of Kejawen. This Slametan is destined for a family whose number and sex sequence of sons belongs to the sukers, that is, one who must perform ruwatan to ask for salvation. In the present time, Ruwatan has been abandoned by many people. This is related to the increasing number of Javanese people who make the Shari'a of Islam as a guide of life and begin to abandon the teachings other than that. In every implementation, Ruwatan performed by involving the neighbors and closest relatives. Problems arise when one of the Javanese families intends to hold ruwatan in the midst of a society that begins to leave and does not believe in the tradition. To bridge this, families who want to hold Ruwatan combine the show with Islamic activities. The same thing is done by the puppeteer by combining Batara Kala puppet show with the teachings of Islam, even by reading one verse of the Qur'an. The Dalang also gives a different meaning to the character of Batara Kala which is associated with Islamic teachings about the concept of time. This research was conducted in Sumberejo Village, Gedangan District, Malang Regency, East Java. The research method used in this research is participant observation with in-depth interview.